2007
DOI: 10.1111/j.1365-2710.2007.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patient awareness of selected potential drug interactions with self-medication

Abstract: Efforts to increase awareness of potential drug interactions is needed. Although community pharmacies are adequately equipped with computerized drug interaction surveillance systems this is often not applied to self-medication. Vigilance for potential interactions of all drugs, including those sold over the counter, should be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 14 publications
1
46
2
Order By: Relevance
“…Potential risks arose because a considerable proportion of participants were also taking vitamins and herbal supplements. A study by Indermitte et al [16] in Basel, Switzerland demonstrated that of 1,183 customers, 116 (26.7%) regular customers were exposed to potential drug interactions within their prescribed drugs and in 28 (6.5%) multiple (C2) potential drug interactions were found. Lack of awareness of drug interaction could pose health hazards in terms of adverse reactions and prolonged suffering owing to unintended or unrecognized interaction, as described by Kaufman et al [9].…”
Section: Discussionmentioning
confidence: 97%
“…Potential risks arose because a considerable proportion of participants were also taking vitamins and herbal supplements. A study by Indermitte et al [16] in Basel, Switzerland demonstrated that of 1,183 customers, 116 (26.7%) regular customers were exposed to potential drug interactions within their prescribed drugs and in 28 (6.5%) multiple (C2) potential drug interactions were found. Lack of awareness of drug interaction could pose health hazards in terms of adverse reactions and prolonged suffering owing to unintended or unrecognized interaction, as described by Kaufman et al [9].…”
Section: Discussionmentioning
confidence: 97%
“…They may also have perceptions that OTC medicines are safe and 'too weak to cause any real harm' [8]. Wilcox et al [9] reported that OTC non-steroidal antiinflammatory drug (NSAID) users were generally unaware of the potential for side-effects while Indermitte et al [10] and Ngo et al [11] found that consumers typically had a lack of awareness of potential drug interactions with self-medication.…”
Section: Introductionmentioning
confidence: 98%
“…The use of OTC medicines contributes to relieving the financial burden on healthcare systems: a recent analysis in seven European countries showed that a move of 5% of medicines from prescription to OTC status would generate annual savings exceeding 16 billion Euro [4]. The literature has mainly focused on healthcare professionals' attitudes towards OTC medicines [5][6][7]; the role of the pharmacist in OTC medicine use [8]; the impact of a prescription-to-OTC switch on prescribing patterns and utilization of physician services [9,10]; drug interactions, adverse drug events and misuse of OTC medicines [11,12]. However, there is a paucity of evidence on patient experiences of pharmacy distribution and services related to OTC medicines [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%